Design of Measurement System for Laboratory-Scale Resistivity Meter with ADS1115 and Buffer - Lubis, Lailatul Husna; Kasma, Doan Aditya; Nasution, Mulkan Iskandar (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2025)
A resistivity meter relies on its measurement system as a crucial part that determines the accuracy of data acquisition in geoelectrical methods. Previous developments in digital resistivity meters using voltage sensor modules, INA219 modules, and ACS712 modules have shown limitations in terms of accuracy and the resolution of their analog-to-digital converters (ADC). These shortcomings can be overcome by integrating the ADS1115 module, which converts analog sensor signals into precise digital outputs down to the millivolt range. NodeMCU ESP32 is used to process digital signals from the ADS1115 into current and voltage readings displayed on the LCD; then data monitoring and download can be performed via the website. Measurement data is stored on a microSD card with date and time synchronization from the DS3231 real-time clock (RTC) module. Calibration results show very high linearity in the input range of ±30–500 mA for current and ±0.0005–6.5 V for voltage, with an R² value of 0.999, indicating that the regression equation is can used to describes the sensitivity characteristics of the measurement system. Accuracy tests resulted in an average of 99.8% for the current measurement system and 99.9% for the voltage measurement system, suggesting that sensor readings closely align with the results of standard measuring instruments like multimeters. Prototype testing in laboratory-scale produced inverse modeling graph with the first layer of homogeneous sand samples and the first and second layers of sand mixed with gravel samples in accordance with previous studies, by the RMS error obtained for each sampel were 26.58% and 39.70%.